CORPORATE GOVERNANCE, FIRM SIZE DAN EARNINGS MANAGEMENT - Yuwono, Martinus Ryno Prisilino; Marlinah, Aan (E-Jurnal Akuntansi TSM, 2024)
The aims of this research is to determine empirical evidence regarding the influence of corporate governance, firm size, leverage, sales growth as independent variable to earnings management as dependent variable in listed consumer cyclical and non-cyclical companies on the Indonesia Stock Exchange . Earnings management variable in this research was measured using the Modified Jones Model developed by Dechow et al. This research used a sample of 108 consumer cyclical and non-cyclical sector companies on the Indonesia Stock Exchange for the period 2020-2022 by purposive sampling method.  This research uses multiple regression method to determine relation between each independent variable to variable dependent. The results of this research show that independent variables such as board of director’s,  auditor’s size, firm performance and firm size have effect on earnings management, while other independent variables such as managerial ownership, leverage, sales growth, and audit committee have no effect on earnings management.